Kajian Hukum tentang Kewenangan Legislatif Badan Permusyawaratan Desa dalam Pembentukan Peraturan Desa - Firda Afiana Maghfiroh; Sri Astutik; Noenik Soekorini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Village Consultative Body as a village legislative institution has the function of compiling and enacting regulations together with the village head. BPD also has the authority to legislate, supervise and empower the community as regulated in Law Number 6 of 2014 concerning Villages. Apart from making regulations, the BPD also has the authority to supervise the running of village government, especially in implementing village regulations and implementing the village budget. From the explanation above, the author formulates two problem formulations, namely how the legislative authority of the Village Consultative Body in forming village regulations based on Law Number 6 of 2014 concerning Villages and how to apply the theory of participatory democracy in forming village regulations. The purpose of this research is to analyze and understand the legislative authority possessed by the Village Consultative Body (BPD) in the process of forming village regulations in accordance with the provisions of Law Number 6 of 2014 concerning Villages and analyze the application of participatory descriptive theory by the Village Consultative Body (BPD). in the formation of village regulations. In this research the author uses a type of normative legal research where this research will focus on laws as legal material. The results of this research are that the Village Consultative Body (BPD) as a representative of the community has the authority to play an active role in making village regulations that have been regulated in the Law and active community participation can strengthen the legitimacy of village regulations and improve village governance and there needs to be ongoing efforts to strengthen community participation.